PENGARUH RETURN ON EQUITY, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM DAN NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Rika Maulidah; Ida Subaida; Febri Ariyantiningsih (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine the effect of Return on Equity, Earnings per Share, and Debt to Equity Ratio on stock prices and firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employs purposive sampling as the sampling technique, resulting in a total of 11 sample companies. Data analysis is conducted using SmartPLS 3.0. The data analysis methods used in this study include classical assumption tests, consisting of multicollinearity and normality tests, the coefficient of determination test, structural equation modeling (inner model) analysis, and hypothesis testing. The results of the direct hypothesis testing indicate that Return on Equity, Earnings per Share, and Debt to Equity Ratio have a significant effect on stock prices. Return on Equity and Earnings per Share also have a significant effect on firm value, whereas the Debt to Equity Ratio does not have a significant effect on firm value. In addition, stock prices are found to have a significant effect on firm value. The results of the indirect hypothesis testing show that Return on Equity, Earnings per Share, and Debt to Equity Ratio have a significant effect on firm value through stock prices.